Anti-proliferative activity and apoptotic induction of tannins extracted from Quercus infectoria on oral cancer KB cell lines - Fazil Ahmad, Krishna Mohan Surapaneni, Abeer Mohammed Al-Subaie, Balu Kamaraj (Journal of Applied Pharmaceutical Science, 2024)
The present study aimed to evaluate the phytochemicals in Quercus infectoria ethanolic extract and to test the cytotoxic effect on an oral cancer cell line KERATIN-HeLa cells (KB cells). The cytotoxic potential of tannins extracted from Q. infectoria was tested by cell cycle analysis, transforming growth factor (TGF)-beta expression, matrix metalloproteinase (MMP) by fluorescent activated cell sorte, Caspase 3, and Caspase 9 expression by ELISA in KB cell lines treated with the extract. Specific protein (Bcl-2) and the gene expression in the KB cell line upon tannin treatment were detected by western blot and RT-PCR technique. The Caspase 3 and 9 enzymatic activity was carried out using the ELISA method. Virtual screening and molecular docking analysis were conducted to know the binding affinity against the targets matrix metalloproteinase-2 (MMP-2), NF-kB, and RhoA, which are targets of oral cancer cells. Preliminary screening of Q. infectoria indicates it primarily contains tannins and glycosides. The IC50 value of the ethanolic extract was determined to be 76.82 μg/ml. Analysis of the cell cycle revealed that the extract induced dose-dependent arrest in the G0/G1 phase. It is also revealed that KB cell treatment with the extract led to downregulation of the anti-apoptotic protein Bcl-2. Moreover, TGF beta expression was downregulated, and Caspase 3 and Caspase 9 were up-regulated in a dose-dependent manner. In addition, the extract induced mitochondrial membrane potential and MMP induction. Virtual screening and molecular docking revealed that tannins have a favorable binding affinity against MMP-2, NF-kB p65, and RhoA. The study identified that “6-O-digalloyl-1,2,3,4 tetra-O-galloyl-β-D-glucose,” a gallotannin in Q. infectoria, is responsible for the anti-cancer activity. The results of our study found that Q. infectoria extracts have anti-proliferative and apoptotic induction activity, which can help in novel drug discovery and development to alleviate cancer.
Keywords: Q. infectoria, MTT assay, bioactive compounds, apoptosis, cell cycle analysis